Synergistic Effects of Reserve and Adaptive Personality in Multiple Sclerosis. (6th May 2016) - Roy, Shumita; Schwartz, Carolyn E.; Duberstein, Paul; Dwyer, Michael G.; Zivadinov, Robert; Bergsland, Niels; Powell, Victoria; Weinstock-Guttman, Bianca; Benedict, Ralph H.B.
Abstract: Objectives: Cognitive reserve moderates the effects of gray matter (GM) atrophy on cognitive function in neurological disease. Broadly speaking, Reserve explains how persons maintain function in the face of cerebral injury in cognitive and other functional domains (e.g., physical, social). Personality, as operationalized by the Five Factor Model (FFM), is also implicated as a moderator of this relationship. It is conceivable that these protective mechanisms are related. Prior studies suggest links between Reserve and personality, but the degree to which these constructs overlap and buffer the clinical effects of neuropathology is unclear.Methods: We evaluated Reserve and FFM traits—Neuroticism, Extraversion, Openness, Agreeableness, and Conscientiousness—in a cohort of 67 multiple sclerosis (MS) patients. We also examined the extent to which FFM traits and aspects of Reserve interact in predicting cognitive processing speed.Results: Retrospectively reported educational/occupational achievement was associated with higher Openness, and childhood social engagement was associated with higher Extraversion, Agreeableness, and Conscientiousness. Current involvement in exercise activities and social activities was associated with Extraversion, current involvement in hobbies was associated with Neuroticism, and current receptive behaviors were associated with Agreeableness and Conscientiousness. When tested as predictors, Conscientiousness and childhood enrichment activities interacted in predicting cognitive processing speed after accounting for age, disease duration, disability, and GM volume.Conclusions: Childhood enrichment activities and Conscientiousness have a synergistic effect on cognitive processing speed. Current findings have implications for using psychological interventions to foster both Reserve and adaptive personality characteristics to stave off clinical symptoms in MS. ( JINS, 2016, 22, 920–927)